2013
DOI: 10.1128/jvi.01111-13
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in the Paramyxovirus F Protein That Enhance Fusion Activity Shift the Mechanism of Complement-Mediated Virus Neutralization

Abstract: bParainfluenza virus 5 (PIV5) activates and is neutralized by the alternative pathway (AP) in normal human serum (NHS) but not by heat-inactivated (HI) serum. We have tested the relationship between the fusion activity within the PIV5 F protein, the activation of complement pathways, and subsequent complement-mediated virus neutralization. Recombinant PIV5 viruses with enhanced fusion activity were generated by introducing point mutations in the F fusogenic peptide (G3A) or at a distal site near the F transmem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…A study published in 2010 showed that mutation of a single amino acid in Sendai virus F, which created a hyperfusogenic mutant, was also linked to enhanced pulmonary inflammation in vivo (21). A more recent report on parainfluenza virus 5 described a mechanism by which a single amino acid mutation in F causing greater fusion activity also resulted in differential recognition of the virus by the complement pathway (45). We showed that two amino acid changes in F dramatically altered the host response to RSV.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2010 showed that mutation of a single amino acid in Sendai virus F, which created a hyperfusogenic mutant, was also linked to enhanced pulmonary inflammation in vivo (21). A more recent report on parainfluenza virus 5 described a mechanism by which a single amino acid mutation in F causing greater fusion activity also resulted in differential recognition of the virus by the complement pathway (45). We showed that two amino acid changes in F dramatically altered the host response to RSV.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there are substantial structural differences between immature and mature forms of the viral glycoproteins (Lamb and Jardetzky, 2007; Mottet et al, 1986). Likewise, point mutations that destabilize the F protein can alter the binding of human antibodies and increase dependence on C’ for neutralization (Johnson et al, 2013). Thus, the inherent conformation of the parainfluenza glycoproteins and epitope accessibility due to virion structures could be a major factor in eliciting antibodies that are initially of low avidity and more dependent on C’ for neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why, despite strong activation of C’, the pathway does not progress to virion lysis. This could reflect failure to progress through the C’ pathway to MAC formation or lack of a functional membrane attack complex (MAC) due to the presence of C’ inhibitors within the virion (Johnson et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations